2022
DOI: 10.1108/jkm-10-2021-0782
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia, social inhibition, affectivity, and knowledge hiding

Abstract: Purpose This paper aims to examine the impact of adverse personality traits (alexithymia, social inhibition, negative affectivity) and supervisor knowledge hiding on individual knowledge hiding. This study also explores the moderating role of positive affectivity. Design/methodology/approach Partial least squares path modeling and data collected from 518 Polish employees with higher education and extensive professional experience recruited via an Ariadna survey panel were used to test the research hypotheses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 120 publications
(215 reference statements)
2
19
0
Order By: Relevance
“…Finally, while the proposed model explicated the phenomenon of interest relatively well, it is not comprehensive and may be further extended by including other variables. For example, recent research has emphasized the importance of personal power (Issac et al , 2022), adverse personality traits (Kmieciak, 2022) and mental conditions (Issac et al , 2021) in the context of counterproductive knowledge behavior, which may become interesting additions to the future models.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, while the proposed model explicated the phenomenon of interest relatively well, it is not comprehensive and may be further extended by including other variables. For example, recent research has emphasized the importance of personal power (Issac et al , 2022), adverse personality traits (Kmieciak, 2022) and mental conditions (Issac et al , 2021) in the context of counterproductive knowledge behavior, which may become interesting additions to the future models.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, by relying on a case study approach, they highlighted the pernicious role of major depressive disorder and mood disorders such as mania and showed how these disorders may reinforce employees’ knowledge hiding. Kmieciak (2022) also empirically demonstrated that alexithymia – defined as difficulty identifying and describing one’s feelings – and social inhibition predict knowledge hiding. In a similar vein, Santoro et al (2021) emphasized that employees’ mental health is also a sign of resilience which, in turn, boosts their productive behaviors.…”
Section: Introduction [1]mentioning
confidence: 94%
“…Of these, social work demands are particularly important because counterproductive knowledge behavior is generally conducted in the social environment when employees interact with their fellow coworkers. Employees who possess personality disorders exhibit psychological and social deficiencies that determine their knowledge-related decisions (Kmieciak, 2022). In particular, when they are exposed to situational clues which are associated with workplace stress, their personality disorders are manifested in such a way that they distort these workers’ cognitive, affective, behavioral and biological processes (Lee et al , 2005; Gray et al , 2011) which, in turn, trigger maladaptive behavioral responses (Kovacs and Beck, 1978; Liau et al , 1998) in the workplace.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, the sudden departure of numerous fellow coworkers within a very short time may have a negative psychological effect on the remaining employees, causing anxiety, stress and disappointment. Employees exhibiting such poor mental states are less likely to share their knowledge with others (Issac et al , 2021; Kmieciak, 2022), which may further impede intra-organizational knowledge flows. Fifth, when people work together, they often start socializing; develop workplace friendships which are based on common interests, trust, reciprocal liking and shared values; and eventually create networks of friendship ties connecting multiple coworkers (Sias and Cahill, 1998; Berman et al , 2002; Serenko et al , 2022).…”
Section: The Knowledge-related Impacts Of the Great Resignationmentioning
confidence: 99%